Aortic atresia occurring with complete transposition of great arteries. - McGarry, K M (1980)
Aortic atresia occurring with complete transposition of the great arteries (ventriculoarterial discordance) has not previously been reported. A patient with this condition is described, who is alive and relatively well at the age of 6 years. This survival contrasts conspicuously with that of patients with the far commoner situation of aortic atresia with normally connected great arteries. It is suggested that this difference in longevity is a result of the greater ability of the left ventricle to supply both the systemic and pulmonary circulations.